2012
DOI: 10.4236/ajac.2012.38072
|View full text |Cite
|
Sign up to set email alerts
|

A Stability Indicating HPLC Method for Dronedarone in Bulk Drugs and Pharmaceutical Dosage Forms

Abstract: The objective of the current study was to develop a validated, specific and stability-indicating reverse phase HPLC method for the quantitative determination of Dronedarone and its related substances. The determination was done for active pharmaceutical ingredient and its pharmaceutical dosage forms in the presence of degradation products, and its process-related impurities. The drug was subjected to stress conditions of hydrolysis (acid and base), oxidation, photolysis and thermal degradation per Internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…It is a new active substance, and there is no official pharmacopoeial procedure available [6]. Literature overviews confess that drug was estimated by different analytical strategies such as spectrophotometric [7], highperformance liquid chromatography [8][9][10][11][12][13][14][15][16][17], and liquid chromatography mass spectrometry [18,19] in bulk drugs and formulation of dronedarone. From the review, it was found that there were no reported methods for the estimation of elemental impurity, i.e., nickel in dronedarone.…”
Section: Preparation Of Nickel Standard Stock Solution (Solution A)mentioning
confidence: 99%
“…It is a new active substance, and there is no official pharmacopoeial procedure available [6]. Literature overviews confess that drug was estimated by different analytical strategies such as spectrophotometric [7], highperformance liquid chromatography [8][9][10][11][12][13][14][15][16][17], and liquid chromatography mass spectrometry [18,19] in bulk drugs and formulation of dronedarone. From the review, it was found that there were no reported methods for the estimation of elemental impurity, i.e., nickel in dronedarone.…”
Section: Preparation Of Nickel Standard Stock Solution (Solution A)mentioning
confidence: 99%
“…A literature survey also revealed that the analytical methods were available for the investigation of pharmacokinetics of dronedarone where the content of dronedarone individually and with its active metabolite de-butyldronedarone in human plasma was studied by liquid chromatography-tandem mass spectrometry [7] and HPLC-UV [8] methods respectively. Stability indicating HPLC method reported [9] for dronedarone bulk drugs samples and pharmaceutical dosage forms has been found to be non-selective at our end. In addition, few other methods for the quantitative determination of dronedarone in pharmaceutical dosage forms have also been reported [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…The wavelength selected (288 nm) was also found to be not suitable for the determination of dronedarone and specified impurities. Methods [8,9], were also found to be nonspecific for said impurities determination Thus we felt a need for the development of a new chromatographic method that detect and determine all the potential process and degradation related impurities viz., Imp-1 to Imp-11 present in bulk samples of dronedarone hydrochloride and to achieve the separation of all eleven impurities (Figure 1) from the analyte peak. The new method developed in our laboratory showed separation of all the eleven impurities of dronedarone hydrochloride satisfactorily as shown in Figure 5(b).…”
Section: Mass Spectrometry (Ms)mentioning
confidence: 99%
See 1 more Smart Citation
“…2. They include the synthetic intermediates 3, 5 and 6 and the disulfonamide derivative known as impurity B (7) [9], that is a by product from the sulfonylation step. In addition, debutyldronedarone (8), which is known as the major circulating metabolite after oral administration of Dronedarone, is also included here [10,11].…”
Section: Introductionmentioning
confidence: 99%